2018
DOI: 10.1044/2017_jslhr-s-17-0157
|View full text |Cite
|
Sign up to set email alerts
|

Deep Brain Stimulation of the Subthalamic Nucleus Parameter Optimization for Vowel Acoustics and Speech Intelligibility in Parkinson's Disease

Abstract: https://doi.org/10.23641/asha.5899228.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 86 publications
(99 reference statements)
0
5
0
3
Order By: Relevance
“…Anatomical connections between the sensorimotor cortex and the basal ganglia via a corticostriatal-thalamic loop (Alexander, DeLong, and Strick, 1986) suggest that the basal ganglia, including the STN, may also participate in speech production. Indeed, indirect evidence from lesion literature (Brunner et al, 1982;Damasio et al, 1982;Wallesch et al, 1983;Nadeau and Crosson, 1997), from clinical data on deep brain stimulation (DBS) outcomes (Morrison et al, 2004;Witt et al, 2008;Aldridge et al, 2016;Knowles et al, 2018) and neurological disorders involving the basal ganglia (Logemann et al, 1978;Ho et al, 1998;Walsh and Smith, 2012) implicates the basal ganglia in many aspects of speech production. Direct evidence from electrophysiological recordings of STN activity during speech production shows desynchronization of beta power during articulation of non-propositional speech (Hebb, Darvas, and Miller, 2012), and speech-related changes in single unit firing activity (Watson and Montgomery, 2006;Lipski et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Anatomical connections between the sensorimotor cortex and the basal ganglia via a corticostriatal-thalamic loop (Alexander, DeLong, and Strick, 1986) suggest that the basal ganglia, including the STN, may also participate in speech production. Indeed, indirect evidence from lesion literature (Brunner et al, 1982;Damasio et al, 1982;Wallesch et al, 1983;Nadeau and Crosson, 1997), from clinical data on deep brain stimulation (DBS) outcomes (Morrison et al, 2004;Witt et al, 2008;Aldridge et al, 2016;Knowles et al, 2018) and neurological disorders involving the basal ganglia (Logemann et al, 1978;Ho et al, 1998;Walsh and Smith, 2012) implicates the basal ganglia in many aspects of speech production. Direct evidence from electrophysiological recordings of STN activity during speech production shows desynchronization of beta power during articulation of non-propositional speech (Hebb, Darvas, and Miller, 2012), and speech-related changes in single unit firing activity (Watson and Montgomery, 2006;Lipski et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Lower frequency stimulation (<90 Hz, LFS) is a setting showing beneficial effects especially on speech intelligibility, articulation, general grade of dysarthria and laryngeal coordination [62][63][64][65]. These data were confirmed by Fabbri et al, who showed that LFS improved speech intelligibility both in the absence of L-dopa effect and with concomitant L-dopa intake among patients with severe speech impairment chronically stimulated with conventional high frequency stimulation [66].…”
Section: Stn Dbs Programmingmentioning
confidence: 82%
“…In a recent conference paper, Knowles, Adams, Abeyesekera, Manicinelli, and Jog (2016) investigated the impact of the individual electrical parameters of STN-DBS on multiple acoustic and perceptual speech variables, including F2 slope and intelligibility. They reported that F2 transition extent in diphthongs was significantly correlated with intelligibility, while overall F2 slope was not.…”
Section: Discussionmentioning
confidence: 99%